Ecological aspects of the vectorial control of Chagas' disease in Brazil - João Carlos P. Dias (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
The feasibility and most important ecological aspects of vectorial Chagas' disease control are discussed. The spread and maintenance of this disease involve multiple ecological and sociopolitical factors that must be taken into account when control programs are planned, executed and evaluated. In spite of its complexity, Chagas disease can be controlled using methods that target specific mechanisms of transmission, the most important being vectorial and transfusional. Major ecological problems in Chagas' disease control do not exist, even in the case of the chemical control of triatomine vectors. The main challenges for the Brazilian Control Program at this moment are: its maintenance as a political priority; the threat of peridomestic vectors; and the consolidation of permanent horizontal and participative epidemiological surveillance systems against the vector.